The Effectiveness of Group Counseling Using Stress Inoculation Training and Systemic Desensitization Techniques to Reduce Public Speaking Anxiety - Panggah Utama, Forletus; Japar, Muhammad; Awalya, Awalya (Jurnal Bimbingan Konseling, 2021)
Public speaking anxiety was experienced by many santriwati in the Roudlotussalam Islamic Boarding School, Banjarnegara Regency. This study aims to to test the effectiveness of group counseling with stress inoculation training and systematic desensitization techniques to reduce public speaking anxiety for santriwati. 21 students involved in experimental research with a randomized pretest-posttest comparison group design. The results of Wilcoxon and Kruskal Wallis tests point out that group counseling using stress inoculation training technique, systematic desensitization technique, and a combination of the two effectively reduce santriwati’s public speaking anxiety. Group counseling with the stress inoculation training technique is more effective to carry out than the systematic desensitization and the combined techniques. This study recommends the use of stress inoculation training technique to reduce students’ public speaking anxiety.